MOTIVASI KERJA DAN GAYA KEPEMIMPINAN UNTUK KINERJA KARYAWAN HOTEL AMARIS MUARA BUNGO - Ariyanto. M,; Syahwami,; Zulkifli,; Hamirul,; Widya Pratiwi,; Melisa, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This article aims to find out how much influence work motivation and leadership styles have on employee performance at the Amaris Muara Bungo hotel. With a response of 40 people and data collection techniques with a questionnaire. The method used uses associative with multiple linear regression analysis. The results of the research are based on the results of partial hypothesis research showing that the variable work motivation (X1) influences employee performance. This result is proved by tcount for work motivation variable of 2,469> 2,024 and significant value of 0.014 <0.05; Based on the results of partial hypothesis research shows that the leadership style variable (X2) influences employee performance. This result is evidenced by the tcount for the leadership style variable of 2,356> 2,024 and a significant value of 0.024 <0.05; Based on the results of the calculation of the f test simultaneously shows that the value of f arithmetic> F table that is (7,472> 3,245) with a significant 0.002 <0.05, so it can be concluded that the variables of work motivation (X1) and leadership style (X2) on employee performance can affect the level of employees employee performance. Based on the calculation results show that the value of R Square is 0.288. this shows that the variable work motivation and leadership style as a whole has an effect of 28.8% on employee performance